Cloud liquid water path and radiative feedbacks over the Southern Ocean. Issue 20 (28th October 2016) - Bodas‐Salcedo, A.; Andrews, T.; Karmalkar, A. V.; Ringer, M. A.
Abstract: Climate models show a robust shortwave negative feedback in the midlatitude oceans in climate change simulations. This feedback is commonly attributed to an increase in cloud optical depth due to ice to liquid phase change as the climate warms. Here we use a cyclone compositing technique to show that the models' cloud liquid water path (LWP) response is strongly dependent on cloud regime. The radiative and LWP responses are not as tightly coupled as a zonal‐mean analysis would suggest, implying that the physical mechanisms that control the overall LWP response are not necessarily responsible for the radiative response. The area of the cyclone dominated by low‐level stratiform and shallow convective clouds plays a dominant role in the radiative response. Since these are mostly supercooled liquid clouds, the strength of a negative cloud phase feedback in the real world should be smaller than the one predicted by current models. Key Points: LWP and shortwave radiative feedbacks depend on cloud type Cloud phase changes may not be the main mechanism that controls shortwave radiative feedbacks in the midlatitudes Models probably overestimate the intensity of the negative cloud phase feedback